Biohydrogen Production by Antarctic Psychrotolerant Klebsiella sp. ABZ11 - Mohammed, Abdullahi; Abdul-Wahab, Mohd Firdaus; Hashim, Mazlan; Omar, Abdul Hafidz; Md Reba, Mohd Nadzri; Muhamad Said, Mohd Farid; Soeed, Kamaruzaman; Alias, Siti Aisah; Smykla, Jerzy; Abba, Mustapha; Ibrahim, Zaharah (Polish Society of Microbiologists, 2018)
Lower temperature biohydrogen production has always been attractive, due to the lower energy requirements. However, the slow metabolic rate of psychrotolerant biohydrogen-producing bacteria is a common problem that affects their biohydrogen yield. This study reports on the improved substrate synthesis and biohydrogen productivity by the psychrotolerant Klebsiella sp. strain ABZ11, isolated from Antarctic seawater sample. The isolate was screened for biohydrogen production at 30°C, under facultative anaerobic condition. The isolate is able to ferment glucose, fructose and sucrose with biohydrogen production rate and yield of 0.8 mol/l/h and 3.8 mol/g, respectively at 10 g/l glucose concentration. It also showed 74% carbohydrate uptake and 95% oxygen uptake ability, and a wide growth temperature range with optimum at 37°C. Klebsiella sp. ABZ11 has a short biohydrogen production lag phase, fast substrate uptake and is able to tolerate the presence of oxygen in the culture medium. Thus, the isolate has a potential to be used for lower temperature biohydrogen production process.